Biochemical responses associated with resistance to bacterial stalk rot caused by Dickeya zeae in maize. Issue 11 (8th September 2017) - Kumar, Adesh; Hunjan, Mandeep S.; Kaur, Harleen; Dhillon, Harminder K.; Singh, Pushpinder P.
Abstract: Bacterial stalk rot (BSR) of maize caused by Dickeya zeae is an important disease in northwest region of India. In the current study, eighty maize lines were evaluated for resistance against this disease. Of these, 20 were moderately resistant, 25 were moderately susceptible and the rest were highly susceptible to BSR. Six lines from each set were randomly selected. Activities of three antioxidant enzymes, viz. phenylalanine ammonia lyase (PAL), peroxidase (POX) and polyphenol oxidase (PPO) were analysed from these three sets of maize lines representing different levels of resistance. A trend of elevated activity of PAL, POX and PPO was observed in all the three sets of maize lines. The results showed significantly more activity of these three enzymes in moderately resistant than highly susceptible maize lines. The activity of PAL and PPO peaked after 48 hr and of POX after 72 hr of challenge inoculation by D. zeae in all the maize lines. The activity of these enzymes further correlated negatively with disease development. Our results show that PAL, POX and PPO play an important role in contributing towards resistance in maize against BSR.